The house of Fourni on Delos: an interdisciplinary approach on a multi-functional complex - Martz , Anne-Sophie; Wurmser , Hélène (Journal of Greek Archaeology, 2024)
This paper presents some of the results of an ongoing study of the house of Fourni on Delos (Greece), a large architectural complex, built and inhabited from the end of the 2nd to the middle of the 1st centuries BC, in which multiple use and functions are attested. Our work is based on an interdisciplinary approach combining the study of the architecture and the instrumentum of the house, in order to understand the chronology of its occupation, its use and its social and cultural background. Ph. Bruneau previously used such an approach, with tremendous results, for the study of the Delian insula of the house of the Comedians, as well as N. Cahill in his major analysis of the Olynthian houses. We will focus here on two aspects of the multi-functional nature of the house of Fourni, first on the fact that the house is an early example of the combination of a luxurious living area, with all the signs of dignitas, and agricultural / commercial installations, and then, on the results of an investigation into the identification of cooking areas, based on contextualized archaeological findings. These two aspects will enable us to examine the economic role of this particular house in its natural and built environment, as well as the different categories of people it housed.